Metal extraction from spent lithium-ion batteries (LIBs) at high pulp density by environmentally friendly bioleaching process - Roy, Joseph Jegan (2021)
Spent lithium-ion batteries (LIBs) are more hazardous due to the presence of several toxic metals such as cobalt, lithium, nickel, manganese, etc. as well as electrolytes such as LiPF , LiBF , or LiClO . However, these spent LIBs are the secondary source of metals that can be extracted and reused in many ways to decrease their potential environmental risks. Metal extraction from the mixture of LiCoO -based spent LIBs at a high pulp density by bioleaching is challenging because of microbial inhibition due to high metal toxicity and substrate (iron) limitation. In the present study, we have investigated the bioleaching of a mixture of LiCoO -based LIBs at high pulp density (100 g/L) using cost-efficient autotrophic bacteria Acidithiobacillus ferrooxidans. By increasing the biogenic H SO production in the culture media, as well as replenishing the bacterial culture for three cycles, we could recover 94% cobalt and 60% lithium in 72 h at 100 g/L pulp density. The X-ray diffraction (XRD), Scanning electron microscope (SEM), and Inductively coupled plasma - optical emission spectrometry (ICP-OES) analysis of LIB powder before and after bioleaching confirmed that more than 90% cobalt leached out from the LIB powder. This bioleaching process is an environmentally friendly way of extracting metals from the mixture of LIBs in gadgets and can be used for all types of spent LIBs.